2019
DOI: 10.1002/gps.5199
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive resilience among APOE ε4 carriers in the oldest old

Abstract: Objectives Relatively few APOE ε4+ carriers survive to old age (age 80+) without cognitive impairment (CI); thus, little is known about distinguishing characteristics of resilient APOE ε4+ carriers. Herein, we describe the sociodemographic characteristics of a large sample of resilient APOE ε4+ women from the Women's Health Initiative Memory Study (WHIMS) and compare them to noncarriers and APOE ε4+ women who developed CI before age 80. Methods Women were recruited for clinical trials evaluating postmenopausal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Reverse causality is a possible explanation as low cholesterol may be secondary to the pathophysiologic processes related to dementia itself (including altered cholesterol metabolism in the brain) [42] or may reflect worse overall health and nutrition seen in later stages of dementia. Most recently, in a study of resilience factors in APOE4-positive women, levels of total cholesterol and LDL were significantly higher in APOE4 dementia-free survivors compared with non-APOE4 carriers [43].…”
Section: Discussionmentioning
confidence: 99%
“…Reverse causality is a possible explanation as low cholesterol may be secondary to the pathophysiologic processes related to dementia itself (including altered cholesterol metabolism in the brain) [42] or may reflect worse overall health and nutrition seen in later stages of dementia. Most recently, in a study of resilience factors in APOE4-positive women, levels of total cholesterol and LDL were significantly higher in APOE4 dementia-free survivors compared with non-APOE4 carriers [43].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that up to 70% of cognitively normal (CN) individuals have some degree of AD pathology at death and about 30% of these CN individuals meet the criteria for intermediate or high ADNC [ 1 , 7 , 8 , 23 , 58 ]. These CN individuals with intermediate to high ADNC are often described as “cognitively resilient.” Investigations into the unique characteristics of these resilient people have ranged from studies of their clinical and lifestyle differences [ 1 , 10 , 21 , 42 ], neuropathologic differences [ 26 , 43 , 50 ], genetic differences [ 15 , 47 ], brain imaging and metabolic signatures [ 2 , 41 , 51 ], as well as their distinct synaptic characteristics and cytokine profiles [ 6 , 44 , 63 ]. Findings from these studies have revealed higher education levels in the resilient, more engagement in physical and social/mental activities [ 1 , 10 , 42 ], fewer neuropathologic comorbidities [ 1 , 26 , 43 , 50 ], single nucleotide polymorphisms (SNPs) related to immune response, as well as vascular, metabolic and mental health being associated with resilience against amyloidosis [ 15 , 47 ], imaging and metabolic signatures suggesting better maintenance of structure (cortical thickness) and function (FDG-PET) despite AD pathologic change, especially in the anterior cingulate and temporal pole [ 2 , 41 , 51 ], and synapses with fewer tau and Aβ-oligomers in the post-synaptic densities and less ApoE in the pre-synaptic synaptosomes in the resilient [ 44 , 54 , 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the relationship among cognition, dyslipidemia, and APOϵ4, Reitz et al, Hayden et al, 59 and Wei et al 60 described an association among lipid metabolism, AD, and ϵ4 allele, but the mechanisms still require further research and larger sample sizes. 58 60 …”
Section: Discussionmentioning
confidence: 99%